Effect of maleated compatibiliser (PBS-g-MA) addition on the flexural properties and water absorption of poly(butylene succinate)/kenaf bast fibre composites - Ahmad Thirmizir, M.Z.; Mohd Ishak, Z.A.; Mat Taib, R.; Rahim, S. (Universiti Kebangsaan Malaysia, 2013)
Poly(butylene succinate) (PBS) composites with 30 wt.% loading of kenaf bast fibre (KBF) were compatibilised with 5 wt.% maleated PBS (PBS-g-MA). The maleic anhydride (MA) concentration in the compatibiliser was either 3, 5, 7 or 10 phr. In general, the compatibilised composites showed better flexural properties than the un-compatibilised composite. The highest increment in the flexural strength and modulus of 12.7 and 8.9%, respectively, were obtained with the addition of PBS-g-MA with MA concentration of 5 phr. Compatibilised and un-compatibilised PBS/KBF composites were immersed in distilled water for 90 days. The absorption of water by all the composites was observed to follow Fick’s law. The equilibrium moisture content, Mm, of the composites with PBS-g-MA at 3, 5 and 7 phr of MA concentrations was lower than that of the un-compatibilised composite due to improved fiber-matrix interfacial adhesion and reduction of voids content. Both un-compatibilised and compatibilised composites showed dimensional instability after the water absorption. This was probably due to the degradation of the fibre-matrix interfacial adhesion and fibre integrity. The flexural properties of these composites decreased after the water absorption. After re-drying only some of the flexural properties were recovered from plasticizing effect of water.